If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -48 = 1x Reorder the terms: -48 + 5x = 1x Solving -48 + 5x = 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -48 + 5x + -1x = 1x + -1x Combine like terms: 5x + -1x = 4x -48 + 4x = 1x + -1x Combine like terms: 1x + -1x = 0 -48 + 4x = 0 Add '48' to each side of the equation. -48 + 48 + 4x = 0 + 48 Combine like terms: -48 + 48 = 0 0 + 4x = 0 + 48 4x = 0 + 48 Combine like terms: 0 + 48 = 48 4x = 48 Divide each side by '4'. x = 12 Simplifying x = 12
| 4v-16=-9 | | (-27)-(-50)= | | x+x+3x=3 | | 1+6(2+3)= | | 0=-6w+30 | | (-9)-(9)= | | y+14=4 | | (25)-(8)= | | 3(2-3y)+5y=3y | | -[11x-(3x+5)]=-6-[4(3x-4)-2x] | | 3(2x+1)=2(1+3x)-1 | | b-5=0 | | 2=(x-40) | | (19)-(15)= | | (10)-(-30)= | | .2(x+.2)=24 | | -0.5y-7=-7.5 | | (2x+17)+13= | | (32)-(-19)= | | 3900=58x | | 2(x+1)+3(x+2)= | | (23)-(-4)= | | a-13a=6 | | (47)-(33)= | | 21-5x=7-7x | | (.66x+18)=(2x-5) | | 21-5x=7+7x | | (12)-(42)= | | 21-5x=-7+7x | | 4q-15=16q-1 | | 6-x=3x | | 3x+12=-42+6x |